2016
DOI: 10.17756/jfcn.2016-023
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition, Phenolic Profiles and Antioxidant Capacity of Three Common Bean Varieties (Phaseolus Vulgaris L.)

Abstract: Proximate composition, phenolic profiles and antioxidant capacity of three bean varieties (Dimeta, Napirira and Nanyati) were investigated. There were significant (p < 0.05) differences among varieties in all proximate components. Dimeta bean had the highest content of crude fat, and free and bound phenolic compounds, while Nanyati bean had the highest content of ash and carbohydrate. Napirira bean had the highest content of crude protein and all phytochemicals, as well as the oxygen radical absorbance capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…These values are higher than those found by Mosisa (2017) in a study on black climbing beans (P. coccineus) (658.5 g/kg), and by Aremu, Olaofe, Basu, Abdulazeez, and Acharya (2010) who reported values of 531 g/kg in brown Ayocote beans from Nigeria. The carbohydrate content in the Ayocote seeds is close to the range of carbohydrates content in common beans (642.8 and 671.4 g/kg) (Fan & Beta, 2016) and could be a good source of energy. Some significant differences in composition were found which could be due to different cultivars, environmental conditions, and soil characteristics.…”
Section: Proximate Compositionmentioning
confidence: 59%
See 1 more Smart Citation
“…These values are higher than those found by Mosisa (2017) in a study on black climbing beans (P. coccineus) (658.5 g/kg), and by Aremu, Olaofe, Basu, Abdulazeez, and Acharya (2010) who reported values of 531 g/kg in brown Ayocote beans from Nigeria. The carbohydrate content in the Ayocote seeds is close to the range of carbohydrates content in common beans (642.8 and 671.4 g/kg) (Fan & Beta, 2016) and could be a good source of energy. Some significant differences in composition were found which could be due to different cultivars, environmental conditions, and soil characteristics.…”
Section: Proximate Compositionmentioning
confidence: 59%
“…Our values were lower than those previously reported in black beans by (from 21,400 to 79,270 μmol TE/kg). Ayocote beans showed higher ORAC value than those reported in other studies, Oomah et al (2010) found values which ranged from 4100 to 7250 µM TE/kg in beans of different pigmentation, common beans grown in Central Malawi showed values of ORAC from 1800 to 3054 μmol TE/kg (Fan & Beta, 2016) and two Spanish varieties (1313 to 1604 µmol TE/kg) (Pedrosa et al, 2015).…”
Section: Antioxidant Activitiesmentioning
confidence: 62%
“…This creates diverse products with beneficial health effects [ 8 , 9 , 10 ]. An important agricultural group of such raw materials are legumes [ 11 ], which are a valuable source of protein with a balanced amino acid profile, carbohydrates, fiber, vitamins, minerals and phytochemicals with a positive effect on health [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the content and values of the other macronutrients are similar to those reported in other studies for Phaseolus vulgaris L; for example, moisture in the range of 10.4–16.7%, protein 20.1–26.8%; ashes 2.9–5.6%; and carbohydrates in the range of 51.5–61.1% [ 9 , 48 , 49 , 50 , 51 ]. Similarly, [ 52 ] reported moisture information in a range of 8.6–9.6 g/100 g, protein 18.8–21.4 g/100 g, fat 1.7–2.9 g/100 g, ash 3.6–3.8 g/100 g, and carbohydrates 64.3–67.1 g/100 g. In general, in Phaseolus vulgaris L., the protein range expands to between 18 and 30% of the dry weight, with albumins, glutelins, phaseolin, and prolamin being the most abundant.…”
Section: Resultsmentioning
confidence: 99%